ANALISIS PERBEDAAN HARGA SAHAM DAN ABNORMAL RETURN SEBELUM DAN SESUDAH STOCK SPLIT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Abdul Rohim; Anisa Nur Amalia; Widy Taurus Sandy; Achmad Hilal Akbar Ramadhan (STIE PGRI Dewantara Jombang, 2025)
This study aims to determine the difference in stock prices and abnormal returns before and after stock splits in companies listed on the Indonesia Stock Exchange for the period 2022-2024. The data utilized in this study is secondary data. The population in this study were 37 companies. The method of analysis used the Wilcoxon Signed Rank Test. The results of this study show that there is no fluctuation between stock prices before and after stock splits in both the 5-day and 3-day observation periods. But there is a change in the value of the abnormal return before and after the stock split both in the 5-day and 3-day observation periods in companies listed on the IDX for the 2022-2024 period.